Transformational Leadership and the Challenges of Educational Digitalization: A Systematic Literature Review (2020-2025) - Shakila Kausar; Muhamad Arif; Saliha Sebgag (Nidhomul Haq : Jurnal Manajemen Pendidikan Islam, 2025)
Transformational leadership has an ideal role in managing education in the digital era; the need for education to transform from various digitalization challenges should be noted for making decisions by prioritizing the vision and goals of education in the digital era. Hence, the purpose of this study is to analyze the role of transformational leadership in encouraging digital innovation in the world of education, analyze the characteristics of effective transformational leadership in supporting technology integration in the world of education, and examine the challenges faced by educational leaders in implementing digital innovation based on transformational leadership. The research method used is a systematic literature review, which analyzes articles from 2020-2025 through PRISMA analysis. The study found that a leader’s role starts with channeling positive attitudes with a clear vision, driving change, motivators and inspirators, role models/examples, and becoming a foundation for building a sustainable organizational culture. So several characteristics of leaders were found, such as Idealized Influence, Inspirational Motivation, Intellectual Stimulation, Individualized Consideration, Digital Competence, and Visionary Leadership. However, in terms of implementation, several challenges are still found, ranging from digital competency gaps, lack of digital literacy, limited infrastructure, resistance to change, lack of ongoing training, and lack of understanding of AI and the theoretical implications of this study are the development of Bass and Avolio’s theory on the characteristics of transformational leadership through Four I’s: idealized influence, inspirational motivation, intellectual stimulation and individualized consideration, by adding one character that is in line with the challenges of education in the digital era, namely digital competence and visionary leadership with the abbreviation Four I’s and DV.